Fabrication of N, B‐codoped Graphene Aerogel/PPy Composites for Asymmetric Supercapacitor. Issue 42 (8th November 2021) - Xin, Qing; Yu, Jie; Lin, Jun; Zang, Yue
Abstract: We report a facile, low‐cost approach to fabricate N, B‐codoped graphene aerogel/PPy composites for an asymmetric supercapacitor. The supercapacitor is based on the traditional sandwich‐like structure composed of NBGA@PPy‐TB as anode material and PPy‐TB as cathode material. Analysis of NBGA@PPy‐TB microstructure reveals that the PPy‐TB is successfully coated onto the NBGA. The 3D cross‐linked networking structures and heteroatom composition endow the NBGA@PPy‐TB electrode with high specific capacity (566 F/g at 1 A/g). The electrochemical properties of asymmetric all‐solid supercapacitor, such as capacitance, impedance, cycling stability, are discussed. The supercapacitor exhibits a fair specific capacity (160.3 F/g at 0.5 A/g). Abstract : We synthesize trypan blue doped polypyrrole (PPy‐TB) via in‐situ polymerization and N, B co‐doped graphene aerogel (NBGA) via hydrothermal reaction, and report a facile, low‐cost approach to fabricate NBGA@PPy‐TB composites for an asymmetric supercapacitor. The supercapacitor is based on a traditional sandwich‐like structure composed of NBGA@PPy‐TB as anode material, polyvinyl acetate‐sulfuric acid solid (PVA‐H2 SO4 ) as electrolyte and PPy‐TB as cathode material. This assembly strategy of supercapacitor provides a fresh perspective on supercapacitors for energy storage applications.